The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1590/s0104-66321998000100008
|View full text |Cite
|
Sign up to set email alerts
|

Integral Transform Solution for the Forced Convection of Herschel-Bulkley Fluids in Circular Tubes and Parallel-Plates Ducts

Abstract: The thermal entry region in laminar forced convection of Herschel-Bulkley fluids is solved analytically through the integral transform technique, for both circular and parallel-plates ducts, which are maintained at a prescribed wall temperature or at a prescribed wall heat flux. The local Nusselt numbers are obtained with high accuracy in both developing and fully-developed thermal regions, and critical comparisons with previously reported numerical results are performed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…However, the comparison between our results and those resulting from the analytical study carried out by Quaresma and Macêdo [29] (seen Table 5), has shown a deviation in our friction factor values not exceeding 0.4%. This deviation can be argued by the difference existing in the limit of weak shearing between the continuous viscoplastic equation (Eq.…”
Section: The Yield Shear Stress Influence On the Axial Velocity Profilessupporting
confidence: 58%
See 2 more Smart Citations
“…However, the comparison between our results and those resulting from the analytical study carried out by Quaresma and Macêdo [29] (seen Table 5), has shown a deviation in our friction factor values not exceeding 0.4%. This deviation can be argued by the difference existing in the limit of weak shearing between the continuous viscoplastic equation (Eq.…”
Section: The Yield Shear Stress Influence On the Axial Velocity Profilessupporting
confidence: 58%
“…We thus note that the increase in Re causes Table 5 Friction factor (f Re) for various values of the Bingham number. (,) present work, (*) Quaresma and Macêdo [29]. a lengthening of the development length, an effect which is substantially reduced by the existence of a yield shear stress.…”
Section: The Influence Of the Inertia On The Axial Velocity Profilesmentioning
confidence: 50%
See 1 more Smart Citation
“…It is the Generalized Integral Transform Technique -GITT [3], a method which has been used successfully to solve several diffusive problems such as those dealing with the flow in ducts with irregular geometries [4,5], with time varying coefficients and problems involving space dependence for the boundary conditions [6,7], problems with thermally and hydrodynamically developing flows [8,9], diffusive problems involving moving boundaries [10,11], problems of non-Newtonian fluid flows [12,13], among others.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Graetz problem has been extended over problems that focus on turbulent flows [33,[41][42][43][44][45][46], slip flows [7,16,20,37], non-Newtonian flows [9][10][11][12]23,24,27,31,34,38], and forced convection in a porous medium [18,25,[27][28][29] and that include streamwise heat conduction [5,16,18,19,[23][24][25]28,29,39,[41][42][43][44][45][46], and viscous dissipation [1][2][3][4]9,10,16,18,[...…”
mentioning
confidence: 99%